2016
DOI: 10.1080/09638237.2016.1207234
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes towards dementia in adolescent students

Abstract: Background: Improving people's knowledge, perceptions and attitudes of dementia

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 7 publications
2
36
0
1
Order By: Relevance
“…Activities that increase awareness of dementia have been encouraged to promote social inclusion for people with dementia. Previous studies have reported that these activities have had positive effects on the inclusion of people with dementia, as well as on the frequency of contact with individuals with dementia and the public's knowledge of dementia . Knowledge has also been reported to decrease stigma, which could lead to social acceptance of dementia .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Activities that increase awareness of dementia have been encouraged to promote social inclusion for people with dementia. Previous studies have reported that these activities have had positive effects on the inclusion of people with dementia, as well as on the frequency of contact with individuals with dementia and the public's knowledge of dementia . Knowledge has also been reported to decrease stigma, which could lead to social acceptance of dementia .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that these activities have had positive effects on the inclusion of people with dementia, as well as on the frequency of contact with individuals with dementia and the public's knowledge of dementia. [3][4][5][6][7][8][9] Knowledge has also been reported to decrease stigma, which could lead to social acceptance of dementia. 10 However, some studies have shown that knowledge does not always lead to acceptance, and further promotion of activities that increase awareness is encouraged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly important as interventions to tackle stigma towards dementia at an early age are thought to be key to developing positive attitudes . More effort is required to ensure that dementia is embedded into school curriculums, to improve education around dementia. However, to evaluate the impact of educational initiatives, validated measures are required.…”
Section: Discussionmentioning
confidence: 99%
“…However, a UK government poll indicated that over half of the 8 to 17 year olds surveyed stated that if people understood more about dementia, life would improve for those affected and an Alzheimer's Society survey found that 65% of the children surveyed said they believed people living with dementia should be supported and included in everyday life . A further study demonstrated that in schools without dementia on the curriculum, students may have negative attitudes and poor knowledge about the condition . Out of 15 questions testing knowledge about dementia, participants were able to answer just over 6 correctly on average.…”
Section: Introductionmentioning
confidence: 94%